2019
DOI: 10.1177/1753466618823440
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulmonary arterial hypertension with the dual endothelin receptor antagonist macitentan: clinical evidence and experience

Abstract: Macitentan (10 mg once daily orally), a dual endothelin receptor antagonist (ERA) developed by modifying the structure of bosentan to increase the efficacity and safety, is approved for the treatment of pulmonary arterial hypertension (PAH). The pivotal SERAPHIN trial, (a landmark trial in the history of PAH trials because of the large number of included patients, the long-term follow up and the first trial with morbidity/mortality as the primary endpoint) showed a reduction of the risk of a morbidity or morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
(94 reference statements)
1
15
0
Order By: Relevance
“…11,14 Currently available ERAs differ in their endothelin receptor specificity and binding properties, tissue penetration, and other pharmacologic characteristics, which theoretically could be associated with different outcomes. 15,16 However, survival was not assessed as a separate endpoint in the pivotal trials for the ERAs bosentan (Study 351 and BREATHE-1) and ambrisentan (ARIES-1 and -2). [17][18][19] The primary endpoint for all of these trials was a change in exercise capacity (6-min walk distance).…”
Section: Introductionmentioning
confidence: 99%
“…11,14 Currently available ERAs differ in their endothelin receptor specificity and binding properties, tissue penetration, and other pharmacologic characteristics, which theoretically could be associated with different outcomes. 15,16 However, survival was not assessed as a separate endpoint in the pivotal trials for the ERAs bosentan (Study 351 and BREATHE-1) and ambrisentan (ARIES-1 and -2). [17][18][19] The primary endpoint for all of these trials was a change in exercise capacity (6-min walk distance).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelin-1 is a key mediator of PAH, causing proliferation and vasoconstriction in pulmonary vascular smooth muscle cells, and proliferation and vasodilation in pulmonary endothelial cells ( Sitbon and Morrell, 2012 ). Macitentan, derived from the structure of bosentan, is generally well tolerated ( Keating, 2016 ; Belge and Delcroix, 2019 ) and was reported to significantly reduce morbidity and mortality ( Pulido et al, 2013 ; Kim et al, 2016 ). The most frequent adverse events associated to macitentan included anemia, nasopharyngitis, bronchitis and headache ( Belge and Delcroix, 2019 ), whereas adverse effects on liver function were observed for bosentan ( Keating, 2016 ; Kuang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macitentan, derived from the structure of bosentan, is generally well tolerated ( Keating, 2016 ; Belge and Delcroix, 2019 ) and was reported to significantly reduce morbidity and mortality ( Pulido et al, 2013 ; Kim et al, 2016 ). The most frequent adverse events associated to macitentan included anemia, nasopharyngitis, bronchitis and headache ( Belge and Delcroix, 2019 ), whereas adverse effects on liver function were observed for bosentan ( Keating, 2016 ; Kuang et al, 2018 ). Compared to other ERAs, macitentan has been shown ten times more potent than bosentan in lowering blood pressure ( Iglarz et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macitentan is a dual endothelin receptor antagonist which has been approved for the treatment of PAH in adults, but is used off-label in children. Macitentan is able to penetrate deeper into the tissure and and also binds longer to the ETA receptor compared with bosentan (60). A single center prospective study in a cohort of 13 patients aged 12 to 35 years over 24-week showed a beneficial effect of a switch from bosentan to macitentan with respect to exercise capacity (61).…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 99%